Preparation, Characterization And Application Of Hybrid Polymer In Dye Wastewater Treatment - Yeap, Kiew Lee (2014)

(untitled)
Inorganic-organic hybrid polymers, polyaluminium chloride-poly(3- acrylamido-isopropanol chloride) (PACl-PAMIPCl) were prepared, characterized and applied for Reactive Cibacron Blue F3GA (RCB), Disperse Terasil Yellow W- 4G (DTY) and industrial textile wastewaters treatment. The PAMIPCl copolymers were prepared by varying the molar ratio of epichlorohydrin (EPI) to acrylamide (AM). Polimer hibrid organik-bukan organik, polyaluminium klorida-poli (3- acrylamido-isopropanol klorida) (PACl-PAMIPCl) disediakan, dicirikan dan digunakan untuk pengolahan air sisa pewarna Reaktif Cibacron Biru F3GA (RCB), Dispersi Terasil Kuning W-4G (DTY) dan industri tekstil. Copolimer PAMIPCl telah disediakan dengan mengubah nisbah molar epichlorohydrin (EPI) dengan acrylamide (AM).